Willet be one species or two? A genomic view of the evolutionary history of Tringa semipalmata. (13th July 2016) - Oswald, Jessica A.; Harvey, Michael G.; Remsen, Rosalind C.; Foxworth, DePaul U.; Cardiff, Steven W.; Dittmann, Donna L.; Megna, Libby C.; Carling, Matthew D.; Brumfield, Robb T.
Abstract: The Willet ( Tringa semipalmata ; Scolopacidae) is composed of 2 morphologically and vocally distinct subspecies with broadly disjunct breeding distributions in North America. Nominate T. s. semipalmata breeds in coastal salt and brackish marshes along the Atlantic and Gulf coasts of eastern North America and the West Indies, and T. s. inornata breeds in wet grasslands and prairies in the northwestern interior of North America. To assess divergence and test for hybridization between the 2 subspecies, we sampled breeding and wintering populations and collected morphological data, mitochondrial DNA sequences from the ND2 locus, and nuclear DNA sequences from genomic libraries enriched for ultraconserved elements (UCEs). Mitochondrial haplotypes were reciprocally monophyletic between the 2 subspecies and indicated divergence approximately 700, 000 yr ago. The UCE dataset included 4, 635 loci containing 19, 322 single nucleotide polymorphisms (SNPs), and, based on these data, individuals clustered by subspecies with no evidence of admixture between them and no substructure within subspecies. We identified 42 nuclear loci that contained SNPs fixed for alternate alleles between the 2 subspecies. Of the 42 loci with fixed differences, a statistically disproportional 17 were Z-linked, indicating a role for sexual selection in the divergence of the 2 subspecies. Genetic, morphological, ecological, and behavioral differences suggest that the 2 Willet subspecies may merit treatment as separate species. Further studies are needed to determine the presence of pre- or post-mating reproductive isolation.